Science Meeting 2013, Bodega Bay (USA) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The 2013 science meeting aimed to showcase past and on-going participatory work and experiences from CCAFS and the wider CGIAR, and develop ways in which participatory (social learning) approaches could inform and improve current and future CCAFS work. It was held in Bodega Bay (CA), USA, 18-19 March 2013.